Combined effect of pulsed electric field and osmotic dehydration pretreatments on mass transfer and quality of air‐dried pumpkin. Issue 11 (17th October 2022) - Paraskevopoulou, Eleni; Andreou, Varvara; Dermesonlouoglou, Efimia K.; Taoukis, Petros S.
Abstract : Abstract: Pulsed electric field (PEF) and osmotic dehydration (OD) pretreatment can accelerate the time‐consuming drying process and minimize its high energy demands. The effect of PEF and OD pre‐processing conditions and osmotic solution composition on mass transfer kinetics (water loss, solid gain, water activity) and quality properties (color, texture, total sensory quality) during OD and subsequent air‐drying (AD) of pumpkin was studied. Application of PEF (2.0 kV/cm–1500 pulses ) significantly enhanced mass transfer during subsequent air‐drying (increased effective diffusivity coefficient D es and drying rate k drying, respectively). PEF and OD treatments led to a significant reduction of the processing time by 12 and 10%, respectively ( p < 0.05). The maximum reduction of processing time by 27% ( p < 0.05) (compared to untreated sample) resulted in combined use of PEF and OD as pretreatments prior to AD. When PEF pretreatment was combined with OD prior to AD, the corresponding energy was by 50% less than the respective energy required for nonprocessed samples. Practical Application: Pulsed electric fields (PEF) and osmotic dehydration (OD) can be applied for the production of air‐dried pumpkin cuts of superior quality (in terms of quality and sensory characteristics) and reduced energy requirements (as a result of total processing time decrease).